Vascular Contribution to Alzheimer Disease: Predictors of Rapid Progression - Diomedi, Marina; Misaggi, Giulia (CNS & Neurological Disorders - Drug Targets, 2013)
Different courses of Alzheimer disease are observed in clinical practice. The rapidly progressive form could be associated with the presence of a major microcirculatory involvement and hemodynamic insufficiency. This short review aims to provide an overview of the current knowledge of cerebrovascular contribution to Alzheimer disease presentation and progression, hypothesizing the possible vascular markers of rapidly progressive form.
Keywords: transcranial Doppler